2016
DOI: 10.1038/srep31584
|View full text |Cite
|
Sign up to set email alerts
|

Globin mRNA reduction for whole-blood transcriptome sequencing

Abstract: The transcriptome analysis of whole-blood RNA by sequencing holds promise for the identification and tracking of biomarkers; however, the high globin mRNA (gmRNA) content of erythrocytes hampers whole-blood and buffy coat analyses. We introduce a novel gmRNA locking assay (GlobinLock, GL) as a robust and simple gmRNA reduction tool to preserve RNA quality, save time and cost. GL consists of a pair of gmRNA-specific oligonucleotides in RNA initial denaturation buffer that is effective immediately after RNA dena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
5
34
0
Order By: Relevance
“…The GB applied in QuantSeq library construction successfully reduced the proportions of HBA and HBB reads and showed optimum efficiency with concentrations C1 and C2 of the globin blocker compared to higher concentrations ( Figure 2). The GB more than doubled the proportion of reads that mapped to non-globin genes and this led to an increase in the number of detected genes (Figure 3), which agrees with previous studies on globin depletion in RNAseq [10,[12][13][14]. There were, however, some genes which were detected in the NGB samples but not in the corresponding GB samples, but these genes did not show sequence similarity with HBA or HBB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The GB applied in QuantSeq library construction successfully reduced the proportions of HBA and HBB reads and showed optimum efficiency with concentrations C1 and C2 of the globin blocker compared to higher concentrations ( Figure 2). The GB more than doubled the proportion of reads that mapped to non-globin genes and this led to an increase in the number of detected genes (Figure 3), which agrees with previous studies on globin depletion in RNAseq [10,[12][13][14]. There were, however, some genes which were detected in the NGB samples but not in the corresponding GB samples, but these genes did not show sequence similarity with HBA or HBB.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that globin depletion methods in RNA sequencing such as GLOBINclear TM (ThermoFisher), the modified GR protocol (Affymetrix), and GlobinLock are effective in reducing globin mRNA in blood [10,[12][13][14]. However, these studies used a small number of samples and could not validate that the globin depletion method worked uniformly across samples.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, though, one of the key challenges of the analysis of whole blood transcriptome is the overabundance of globin mRNA, which may decrease the ability to detect transcripts with low expression levels. Several experimental protocols of globin depletion have been proposed, which however significantly reduce the amount of extracted RNA following depletion [15] and compromise the quality of the nucleic acid [16]. Any loss of RNA caused by depletion might affect the sequencing data, particularly for samples with a limited amount of starting material.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting amounts and purity of reticulocytes were sufficient for the efficient, high quality RNA isolation required in the NGS‐based transcriptome analyses (Table and Figure ). It should be noted that in the case of reticulocytes obtained from healthy individuals (where extensive hemolysis of red blood cells is not observed), the addition of globin reduction step may be considered, which can enrich data obtained from next generation sequencing‐based expression profiling …”
Section: Discussionmentioning
confidence: 99%